Retrospective epidemiological surveillance of COVID-19 patients in the Department of Radiodiagnosis in M. G. M. Medical College and Associated Hospitals: an audit - Bhandari, Gaurav; Agrawal, Simran; Talera, Yash (International Journal Of Community Medicine And Public Health, 2022)
Background: Epidemiological surveillance is the cornerstone for the prevention and control of any pandemic. The purpose of the study was using clinical and radiological data of COVID-19 positive patients to describe the clinical features, risk factors, grading of severity on the basis of chest X-ray and their survival outcome. Methods: A retrospective observational study comprising 9100 COVID-19 positive patients was done in the Department of Radiodiagnosis, M.G.M. Medical College and M.Y. Hospital, Indore. Patients' data including demography, clinical findings, vaccination status and imaging findings was collected and assessed in between March 2020 and March 2022. In the descriptive statistical analysis, continuous variables were noted in terms of the mean and standard deviation and nominal variables were noted in terms of percentage. Results: In our study, there were 9100 patients proven with positive COVID-19 disease had abnormal CXRs were detected in 7553 of 9100 patients (83%). In our study, B/L lung involvement (69%) was found to be more with lower lung zone predominance (86.5%) and peripheral predominance opacities (83.7%). The most common finding of chest X-ray pattern is consolidation (65.7%), followed by ground glass opacity (29.0%). Most of the vaccinated patients were found to be in mild category and majority of mild cases didn’t require oxygen support. The chi-square statistic is 79.3372. The result is significant at p<0.05 Conclusions: The chest x-ray severity scoring (CXR-SS) system used in this study is a valuable method of disease prognostication in COVID-19. In our study, we found a significant reverse relationship between chest X-ray severity score and oxygen saturation, which has great clinical importance.